Smart Yoga Mat Integrated with AI: Revolutionizing Yoga Practice with Intelligent Technology - Manas Singhal; Ruchi Varshney; Nishi Singh (Research & Review: Electronics and Communication Engineering, 2026)
Artificial Intelligence (AI) has opened up new possibilities for tracking one’s own fitness and health through wearable and Internet of Things devices. The Smart Yoga Mat described in this study has an embedded AI system that tracks, evaluates, and offers real-time feedback on yoga poses. To improve posture detection and correction accuracy, the technology makes use of pressure sensors, Inertial Measurement Units (IMUs), and AI-based pose estimate algorithms. According to hypothetical trial results, the technology offers individualized support and enhances user posture. While reducing the risk of injury, this technology has the potential to enhance the yoga experience at home. This paper presents a Smart Yoga Mat with AI that provides practitioners with corrected feedback based on real-time posture detection. The gadget tracks users’ weight distribution and touch points while they perform yoga poses using built-in pressure sensors in the mat. AI algorithms assess these sensor inputs to determine pose accuracy, spot deviations and offer tailored guidance through a companion smartphone application. Additionally, by incorporating biometric data, like heart rate, wearable technology enhances fitness tracking. The mat-based method is suitable for residential use in a range of lighting and climatic conditions because it offers a privacy-preserving substitute for camera-based systems. The system’s capacity to enhance posture, boost engagement, and promote regular practice has been demonstrated through testing with users of different skill levels. This invention creates an approachable and interactive method to promote safe, efficient yoga practice at home or in rehabilitation centers by fusing traditional yoga techniques with digital intelligence.